The thirty-seven practices of all Buddhas' sons : translations of the Tibetan rGyal.sras.lag.len so bdun.ma - Rgyal-sras Thogs-med Bzaṅ-po-dpal, 1295-1369 (Library of Tibetan Works & Archives, 1973)
Verse works on Buddhist religious practices; Kadampa and Gelukpa traditions in Lamaism.